OVERCAPACITY MANAGEMENT POLICY TO PREVENT VIOLENCE IN DETENTION (STUDY IN CLASS 1 PRISON MEDAN) - Parulian Sihotang; Rizkan Zulyadi; Serimin Pinem (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses the policy of overcrowding as an effort to prevent violence in the Class I Detention Center (Rutan) Medan. The issues studied include: how the overcrowding policy is implemented in preventing violence between inmates; what are the supporting and inhibiting factors in the implementation of the policy; and how effective are the policies of regulatory arrangement, institutional strengthening, and provision of infrastructure in reducing the number of violence in detention. This study uses an empirical legal research with a qualitative approach, which positions law as a social phenomenon (law in action) and not only as a written norm. The nature of this research is descriptive analytical, namely describing objective conditions in the field while analyzing the relationship between the overcrowding policy and the social dynamics that occur in detention. Data were obtained through interviews, observations, and documentation studies. The results of the study indicate that the implementation of the overcrowding policy has been carried out through the redistribution of inmates, optimization of guidance, and coordination between agencies, but still faces obstacles such as budget limitations, minimal facilities and infrastructure, and bureaucratic institutional structures. Supporting factors such as officer commitment and internal innovation in detention also help reduce the potential for violence. Overall, regulatory reform, institutional strengthening, and infrastructure provision contribute to reducing the risk of violence, although their effectiveness remains suboptimal and requires continuous improvement.